PENERAPAN SANITASI HYGIENE PADA PENGOLAHAN ABON IKAN TUNA ASAP DI UPI IKBAL FAMILY JAYAPURA - Haryati, Kristina (UNIB Press, 2025)
Sanitation hygiene implementation actions must be applied to food processing groups to produce quality products that meet food safety. The purpose of this activity is that the UPI Ikbal Family group can use personal protective equipment and wash their hands as a form of implementing sanitation hygiene during the processing of smoked fish into fish floss. The method of this activity is divided into 2, namely counseling on the importance of using PPE and washing hands, and the practice of processing smoked tuna fish floss. The results showed that all participants used PPE from the beginning to the end of the activity. In the practice of processing smoked tuna fish floss, participants continued to use PPE, and the PPE that was changed every 2 hours was masks and gloves. The conclusion from the implementation of this activity is that the program can provide increased awareness among participants in using simple personal protective equipment (PPE) and implementing proper hand washing before and during the processing of smoked tuna fish floss. So it is hoped that the habit of using PPE and washing hands is not only carried out during the implementation of the activity, but can be applied by the UPI Ikbal Family when producing smoked fish or other smoked fish diversification products. Participants were very enthusiastic and patient in following the smoked tuna floss processing practice activities, which were carried out from morning to night.